2021
DOI: 10.2196/16458
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Physical Activity in Japanese Older Adults Using a Social Pervasive Game: Randomized Controlled Trial

Abstract: Background Pervasive games aim to create more fun and engaging experiences by mixing elements from the real world into the game world. Because they intermingle with players’ lives and naturally promote more casual gameplay, they could be a powerful strategy to stimulate physical activity among older adults. However, to use these games more effectively, it is necessary to understand how design elements of the game affect player behavior. Objective The ai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The experiment found that the social interaction design element of the popularity game may have had some positive effects on promoting physical activity. Subsequently, in 2021, Santos et al [ 18 ] continued with the same study, comparing 2 variations of the same pervasive game over 4 weeks with the same purpose and type of experiment: the test group received social interaction whereas the control group did not. In this test, 20 participants were recruited for this experiment (no social interaction group, n=10; social interaction group, n=10), 18 of whom remained active until the end of the study (no social interaction group, n=9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment found that the social interaction design element of the popularity game may have had some positive effects on promoting physical activity. Subsequently, in 2021, Santos et al [ 18 ] continued with the same study, comparing 2 variations of the same pervasive game over 4 weeks with the same purpose and type of experiment: the test group received social interaction whereas the control group did not. In this test, 20 participants were recruited for this experiment (no social interaction group, n=10; social interaction group, n=10), 18 of whom remained active until the end of the study (no social interaction group, n=9).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, there are pervasive games designed for adults, teachers, and students to learn [ 32 , 44 ]. At the same time, there are pervasive games for older adults, indicating some positive effects on promoting physical activity [ 18 ]. From the literature, it can see some hints of the research tendencies of scholars: in the early days, they studied the pervasive game design experiences of children users, followed by the pervasive game design experiences of adult users, and in recent years, they focused on the pervasive game design experiences of older adult users.…”
Section: Discussionmentioning
confidence: 99%